Circulating growth differentiation factor‐15 levels are associated with early echocardiographic signs of diastolic function impairment in the STANISLAS cohort: A 20‐year follow‐up study - Monzo, Luca; Xhaard, Constance; Ferreira, João Pedro; Baudry, Guillaume; Lamiral, Zohra; Duarte, Kevin; Bozec, Erwan; Boivin, Jean‐Marc; Huttin, Olivier; Rossignol, Patrick; Zannad, Faiez; Girerd, Nicolas (European journal of heart failure, 2025)
Aims Early identification of healthy subjects prone to develop cardiac dysfunction may be instrumental to prevention strategies. Our study aimed to evaluate whether circulating levels of growth differentiation factor‐15 (GDF‐15) could predict adverse changes in echocardiographic indexes of cardiac structure and function in an initially healthy populational familial cohort with a long follow‐up (STANISLAS cohort). Methods and results We evaluated 1679 participants (49 ± 14 years, 48% males) included in the fourth visit (V4) of the STANISLAS cohort with available GDF‐15 measurements (Olink proteomic analysis) and echocardiographic parameters. Among them, 1562 had also GDF‐15 measurements at the first visit (V1) (18.2 ± 1.4 years before V4). We evaluated both prospective (GDF‐15 at V1) and cross‐sectional (GDF‐15 at V4) associations between GDF‐15 levels and echocardiographic variables. In adjusted analyses, higher baseline GDF‐15 levels were associated with lower left ventricular (LV) end‐diastolic volume and higher E/e' ratio nearly two decades later (both p ≤ 0.01). The cross‐sectional analysis at V4 also found significant associations between GDF‐15 and LV end‐diastolic volume and higher E/e' ratio, further identifying significant associations with impaired LV strain. Conclusion In the STANISLAS cohort, initial circulating GDF‐15 levels were associated with echocardiographic signs of reduced LV size and increased filling pressure almost two decades later. This association was also confirmed by evaluating GDF‐15 at the follow‐up visit (V4). These findings suggest a potential role for GDF‐15 as an easy screening and prognostic tool of diastolic dysfunction in the general population. Summary of the study design and key findings. The (+) and (−) signs mean that the variable has a positive or a negative association with growth differentiation factor‐15 (GDF‐15) levels in the fully adjusted model (age, gender, current smoker, body mass index, total cholesterol, systolic blood pressure and N‐terminal pro‐B‐type natriuretic peptide), respectively. LV, left ventricular; LVEDVi, left ventricular end‐diastolic volume index; LV‐GLS, left ventricular global longitudinal strain; LVMi, left ventricular mass index.